2021
DOI: 10.3390/agriculture11111099
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Soil Water and Heat Flow under Plastic Mulching and Different Ridge Patterns

Abstract: The ridge–furrow mulching system with plastic film (RFMS) has been widely used in semi-arid areas in order to improve soil water and heat conditions, crop yields and water use efficiency. It is of practical significance to study the effect of mulching and ridge types on soil water and heat in order to optimize mulching measures and improve the effectiveness of the ridge and furrow system. To clarify the combined effect of soil water and heat beneath the system and the influence of ridge morphology on it, field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Yang et al [33] showed that plastic film mulching can increase the surface soil temperature, especially in the early and middle stages of cotton growth. In the early growth stage (sowing-emergence), the daily average surface soil temperature of the covered plots was 2.5-3.2 • C higher than that of the control group, which may be due to the fact that the plastic film mulching reduced soil moisture evaporation and latent heat flux, thus increasing the soil temperature [34]. The increase in the ground temperature is beneficial to the vegetative growth of cotton and ultimately promotes cotton growth [35].…”
Section: Discussionmentioning
confidence: 95%
“…Yang et al [33] showed that plastic film mulching can increase the surface soil temperature, especially in the early and middle stages of cotton growth. In the early growth stage (sowing-emergence), the daily average surface soil temperature of the covered plots was 2.5-3.2 • C higher than that of the control group, which may be due to the fact that the plastic film mulching reduced soil moisture evaporation and latent heat flux, thus increasing the soil temperature [34]. The increase in the ground temperature is beneficial to the vegetative growth of cotton and ultimately promotes cotton growth [35].…”
Section: Discussionmentioning
confidence: 95%
“…The temporal change in soil temperature is closely related to the growth period of cotton, and PFM can change the latent heat flux, such as cotton population water evaporation and soil water transpiration ( Jiang et al, 2022 ; Li et al, 2021 ), and then increase thermal radiation capture and topsoil temperature, especially in the early and middle stages of cotton growth ( Zong et al, 2020 ; Ghosh et al, 2006 ). In this study, before the initial flowering stage (July 1), especially before the first irrigation (June 20), the temperature of the 0–50 cm soil layer in the cotton field covered with plastic film was higher by approximately 2−4 °C than that in the uncovered cotton field.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Zhao et al (2012) revealed that the daily average surface soil temperature in the covered plots was 2.5−3.2 °C higher than that in the control group in the early growth stage (sowing-seedling). This may be due to the reduction of soil water evaporation and the decrease of latent heat flux by plastic film mulching and then increase the soil temperature ( Li et al, 2021 ). Less obvious effect of PFM on the soil temperature increase (approximately 1−2 °C) of the soil below 50 cm was indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding heat conduction in soil water layers allows farmers and agricultural scientists to decide when to plant, irrigate, or harvest crops. (Balota et al, 2008; Li et al, 2021; Rodríguez et al, 2015) Efficient water use is a global concern. Studying heat conduction in the soil allows for the determination of how various soil types retain or release heat, consequently impacting the moisture content of the soil; this knowledge can help develop precise irrigation strategies.…”
Section: Introductionmentioning
confidence: 99%